2019
DOI: 10.12693/aphyspola.136.495
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Highly Efficient Monolayer MoSe2 Based Solar Cells

Abstract: The effect of MoSe2 thin films on the solar photovoltaic characteristics of ZnO/ZnS/MoSe2 has been studied. The variation in the efficiency of the solar cells as a funcion of the thickness of the MoSe2 layer, characteristic (J-V), and the quantum efficiency (QE) of the solar cell for different energies of the incident radiation have been studied. The results indicate that when the thickness of MoSe2 is increased the efficiency of MoSe2 based solar cells improves from 9.24% to 17.51%. The output photovoltaic pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 25 publications
(25 reference statements)
0
8
0
Order By: Relevance
“…Recently, transition metal dichalcogenides (TMDs) have been getting attraction due to their remarkable optical and electrical features such as tunable bandgap, large absorption coefficient, and suitable transportation of electrons. TMD compounds having monolayer structures, for example, MX 2 , where M, transition metal atom (Mo, W, Nb, Ti), and X, Chalcogen atom, (S, Se, Te) have gained popularity for their use in PV cells. , Furthermore, 2D materials with distinct crystal structures may help build a strong hetero-junction with excellent interfacial properties that are not affected by lattice mismatch . The bandgap of molybdenum disulfide (MoS 2 ) varies from indirect to direct, increasing from 1.2 to 1.8 eV, indicating that the bandgap of MoS 2 is flexible as well as has multiple benefits in optoelectronics .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, transition metal dichalcogenides (TMDs) have been getting attraction due to their remarkable optical and electrical features such as tunable bandgap, large absorption coefficient, and suitable transportation of electrons. TMD compounds having monolayer structures, for example, MX 2 , where M, transition metal atom (Mo, W, Nb, Ti), and X, Chalcogen atom, (S, Se, Te) have gained popularity for their use in PV cells. , Furthermore, 2D materials with distinct crystal structures may help build a strong hetero-junction with excellent interfacial properties that are not affected by lattice mismatch . The bandgap of molybdenum disulfide (MoS 2 ) varies from indirect to direct, increasing from 1.2 to 1.8 eV, indicating that the bandgap of MoS 2 is flexible as well as has multiple benefits in optoelectronics .…”
Section: Introductionmentioning
confidence: 99%
“…1189,1190 Although the excellent capability of solar harvesting has been extensively investigated and TMDC based solar cells have shown excellent conversion efficiency by theoretically modeling, practical solar cells based on a TMDC active layer have rarely been reported. 1191−1195 1196 Significantly improved conversion efficiency was obtained from 9.24% to 17.51% with J sc of 22.19 mA/cm 2 and V oc of 0.8 V. 1196 One of the most promising applications for graphene is use for electrodes ing solar cells and batteries. 1197,1198 Graphene has been well demonstrated to have unique mechanical, electronic, and optical properties, in particular high transparency, flexibility, and electrical conductivity, together with outstanding scalability, modularity, and suitability for roll-toroll fabrication, which enables graphene to be an ideal material for photovoltaic technology.…”
Section: Renewable Energymentioning
confidence: 99%
“…TMDCs are generally regarded as excellent candidates for light harvesting, due to highly efficient light absorption with a direct band gap and strong light–matter interactions. , Although the excellent capability of solar harvesting has been extensively investigated and TMDC based solar cells have shown excellent conversion efficiency by theoretically modeling, practical solar cells based on a TMDC active layer have rarely been reported. Zaidi et al reported TMDC based solar cells with the structure ZnO/ZnS/MoSe 2 and obtained improved performance by optimizing the thickness of MoSe 2 layer . Significantly improved conversion efficiency was obtained from 9.24% to 17.51% with J sc of 22.19 mA/cm 2 and V oc of 0.8 V …”
Section: Metaphotonic Devices Based On 2d Materialsmentioning
confidence: 99%
“…Though, several promising research works reported on TMDCs of MoS 2 , WS 2 , WSe 2 , MoTe 2 , and SnS, applied in solar cells, only layered materials of MoSe 2 with In 2 Te 3 BSF and CdS window layers using dual heterojunction structure have rarely performed yet. Theoretical design and empirical study on the efficacy and versatility of MoSe 2 absorber layer recently conjecture the massive potentiality of MoSe 2 for the fabrication of energy devices and TFSCs [17,18].…”
Section: Introductionmentioning
confidence: 99%